Calcium phosphate ceramic as a model for enamel substitute material in dental applications - Phakvalunch Rujiraprasert; Sarat Suriyasangpetch; Anucharte Srijunbarl; Thawanrat Singthong; Chalermkwan Makornpan; Katanchalee Nampuksa; Thanaphum Osathanon; Dusit Nantanapiboon; Naruporn Monmaturapoj (BDJ Open, 2023)
Abstract Objective This study aimed to develop enamel substitute material using a mechanochemical technique. Materials and Methods Hydroxyapatite was synthesized with and without tricalcium phosphate under uniaxial pressing of 10 and 17 MPa (HA10, HA17, BCP10, and BCP17), followed by sintering at 1250 °C for 2 h. Human enamel and dentin blocks were used as control groups. The mechanical properties were determined by compressive strength test and Vickers microhardness. The data were analyzed with one-way ANOVA and LSD post-hoc test (α = 0.05). The phase formation and morphology of the specimens were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results HA17 and HA10 had compressive strength values comparable to enamel and dentin, respectively (p > 0.05). The microhardness of all synthesized groups was significantly higher than that of tooth structures (p < 0.05). From the XRD graphs, only the hydroxyapatite peak was observed in the control and HA groups. SEM images showed homogeneous hydroxyapatite grains in all groups, while the BCP groups contained higher porosities. Conclusions Both HA10 and HA17 are suitable for use as the inorganic part of dentin and enamel substitutes.